Formation of Cubic Ice via Clathrate Hydrate, Prepared in Ultrahigh Vacuum under Cryogenic Conditions - Ghosh, Jyotirmoy; Bhuin, Radha Gobinda; Vishwakarma, Gaurav; Pradeep, Thalappil (Journal of Physical Chemistry Letters, 2019)
Cubic ice (ice Ic) is a crystalline phase of solid water, which exists in the earth's atmosphere and extraterrestrial environments. We provide experimental evidence that dissociation of acetone clathrate hydrate (CH) makes ice Ic in ultrahigh vacuum (UHV) at 130-135 K. In this process, we find that crystallization of ice Ic occurs below its normal crystallization temperature. Time-dependent reflection absorption infrared spectroscopy (RAIRS) and reflection high-energy electron diffraction (RHEED) were utilized to confirm the formation of ice Ic. Associated crystallization kinetics and activation energy (Ea) for the process were evaluated. We suggest that enhanced mobility or diffusion of water molecules during acetone hydrate dissociation enabled crystallization. Moreover, this finding implied that CHs might exist in extreme low-pressure environments present in comets. These hydrates, subjected to prolonged thermal annealing, transform into ice Ic. This unique process of crystallization hints at a possible mechanistic route for the formation of ice Ic in comets.
CRIS-Team Scopus Importer:2019-12-31